Studi Eksperimental Karakteristik Beton Ringan SCC dengan Penambahan Styrofoam dan Benang Gelasan - Fajrul Falah, Muhammad; Solikin, Mochamad; Kholilur Rohman, Rosyid; Muhammad Nuryanto, Fadhil; Ika Hariani, Deby; Putri Yastari, Febi; Agung Saputra, Cahyo (Jurnal Ilmiah Rekayasa Sipil, 2025)
Global sustainability is a big challenge for various industry sectors, including the construction industry. Concrete is a key material in infrastructure development due to its high strength and good durability. However, concrete production has significant environmental impacts, such as the exploitation of natural resources and increased carbon emissions. Therefore, there is a need to innovate materials that are more environmentally friendly without reducing the quality of concrete. This research aims to explore the use of Styrofoam waste and yarn as additives in concrete mixes. Styrofoam was chosen due to its lightweight and biodegradable nature, its use in concrete can reduce environmental pollution. Meanwhile, yarn was added to increase the strength of concrete that had undergone changes due to the addition of Styrofoam. This research was conducted using an experimental method with the addition of 30% Styrofoam from the total fine aggregate as a fixed variable. In addition, variations of yarn were used at 0.5% and 1% of the total concrete mix. Tests were carried out using cylindrical test objects with a diameter of 15 cm and a height of 30 cm, with a total of 8 samples tested to determine the compressive strength value of the resulting concrete. The test results showed that the highest compressive strength was obtained in the variation of adding 1% yarn, with a value of 15.03 MPa. This shows that the combination of styrofoam and yarn still allows the concrete to have sufficient strength for certain construction applications. From this research, it can be concluded that the use of Styrofoam and yarn in concrete has the potential to be an environmentally friendly material innovation that supports the sustainability of the construction industry. By utilizing this waste, it is expected to reduce environmental impact and open up new opportunities in the development of sustainable construction materials